Kajian Manfaat Diet Mediterania: Analisis - Priskila, Loury; Perkasa, Tengku Arief Buana; Wijaya, Yogik Onky Silvana (PT Kalbe Farma Tbk., 2024)
The rapid growth of nutrigenomics and nutrigenetics has greatly contributed to understanding the importance of genetic, nutrition, and environmental interaction in maintaining human health. Healthy lifestyles such as adequate physical activity and healthy diet patterns have been widely reported may reduce the risk of various diseases. One of the health diet patterns that has been widely studied is the Mediterranean diet (MedDiet). MedDiet is a plant-based diet pattern high in fiber, high in unsaturated fatty acids, and low in meat and dairy products. This literature study aims to summarize the health benefits of the MedDiet pattern and its biomechanisms.